Periprosthetic Joint Infections - Lima, Ana Lucia L.; Oliveira, Priscila R.; Carvalho, Vladimir C.; Saconi, Eduardo S.; Cabrita, Henrique B.; Rodrigues, Marcelo B. (Interdisciplinary Perspectives on Infectious Diseases, 2013)
Implantation of joint prostheses is becoming increasingly common, especially for the hip and knee. Infection is considered to be the most devastating of prosthesis-related complications, leading to prolonged hospitalization, repeated surgical intervention, and even definitive loss of the implant. The main risk factors to periprosthetic joint infections (PJIs) are advanced age, malnutrition, obesity, diabetes mellitus, HIV infection at an advanced stage, presence of distant infectious foci, and antecedents of arthroscopy or infection in previous arthroplasty. Joint prostheses can become infected through three different routes: direct implantation, hematogenic infection, and reactivation of latent infection. Gram-positive bacteria predominate in cases of PJI, mainly Staphylococcus aureus and Staphylococcus epidermidis. PJIs present characteristic signs that can be divided into acute and chronic manifestations. The main imaging method used in diagnosing joint prosthesis infections is X-ray. Computed tomography (CT) scan may assist in distinguishing between septic and aseptic loosening. Three-phase bone scintigraphy using technetium has high sensitivity, but low specificity. Positron emission tomography using fluorodeoxyglucose (FDG-PET) presents very divergent results in the literature. Definitive diagnosis of infection should be made by isolating the microorganism through cultures on material obtained from joint fluid puncturing, surgical wound secretions, surgical debridement procedures, or sonication fluid. Success in treating PJI depends on extensive surgical debridement and adequate and effective antibiotic therapy. Treatment in two stages using a spacer is recommended for most chronic infections in arthroplasty cases. Treatment in a single procedure is appropriate in carefully selected cases.